Experimental Study on Water-Jet Shock Microforming Process Using Different Incident Pressures - James Kwasi Quaisie; Wang Yun; Xu Zhenying; Yu Chao; Fuzhu Li; Philip Baidoo; Joseph Sekyi-Ansah; Emmanuel Asamoah (Advances in Materials Science and Engineering)
The purpose of this paper is to demonstrate a new process technology using the cavitation phenomenon, mainly a water-jet shock microforming, for the fabrication of a metallic foil. 304 stainless steel was exposed to a high-speed submerged water jet with different incident pressures and certain working conditions. In this experiment, a KEYENCE VHX-1000C digital microscope, confocal laser-scanning microscope (Axio CSM 700), and micro-Vickers hardness tester were utilized to observe the forming depth, surface quality, thickness distribution, and section hardness distributions under different incident pressures. The experimental results indicated that the surface morphology of the metal foils attained good geometrical features under this dynamic microforming method and there were no cracks or fracture. The forming depth and surface roughness increased with the incident pressure. In addition, the forming depth increased from 124.7 μm to 327.8 μm, while the surface roughness also increased from 0.685 μm to 1.159 μm at an incident pressure of 8 MPa to 20 MPa. Maximum thickness thinning of the formed foils occurred at the fillet region when the thickness thinning ratio was 21.27% under the incident pressure of 20 MPa, and there was no fracture at the bottom or the fillet region. The tested hardness indicated that during the cold-rolled state of the sample, the hardness sample increased slightly along the cross section of the formed region and the hardness of the annealed 304 stainless steel foils increased significantly along the cross-sectional region.